Company Limited Based on a Novel by Manisankar Mukherjee - Ray, Satyajit; Roy, Soumendu; Tagore, Sharmila; Chanda, Barun; Chowdhury, Parumita (Calcutta Trilogy)
In a marvel of concise exposition, the film's 'prologue' of sorts is communicated almost entirely through voiceover: after graduating with a degree in English from university, Shyamalendu is accepted for a job as marketing manager at a British-owned firm, Hindustan-Peters, selling fans. Married, with a studio flat in Calcutta and a young son at boarding school, Shyamalendu's life is snug, smug and complacent … Until, that is, his lower class sister-in-law turns up, casting a darker, outsider's perspective on his vacuous, shallow set-up. Is Shyamal’s goal of being company director the be-all and end-all of life, or is he sacrificing an essential part of himself? [moviemuser.co.uk]